Biochemical composition, morphology and antimicrobial susceptibility pattern of Corynebacterium pseudotuberculosis biofilm - Yaacob, Mohamad Fakhri; Murata, Aika; Mohamad Nor, Nurul Hidayah; Abdullah, Faez Firdaus Jesse; Raja Yahya, Mohd Fakharul Zaman (Elsevier, 2021)
Caseous lymphadenitis (CLA) is a ruminant disease caused by Corynebacterium pseudotuberculosis, a Gram-positive facultative intracellular pathogen. The present work was performed to investigate the biochemical composition, morphology and antimicrobial susceptibility pattern of C. pseudotuberculosis biofilm using Raman spectroscopy, field emission scanning electron microscopy (FESEM) and microplate biofilm assay respectively. Results showed that the 24-h-old biofilm was characterized by Raman spectral peaks at 615 cm−1 (CCC symmetric bend phenyl ring), 668 cm−1 (Valine) and 825 cm−1 (Ring breath Tyr.) whilst the 48-h-old and 72-h-old biofilms were characterized by Raman spectral peaks at 1400 cm−1 (COOsingle bond sym.), 1450 cm−1 (COOsingle bond sym.), 1581 cm−1 (Ring breath Trp.), 1650 cm−1 (COOsingle bond asym.) and 1725 cm−1 (Cdouble bondO str.). Raman spectra also revealed the biochemical heterogeneity in C. pseudotuberculosis biofilm. FESEM images clearly showed the biofilm cells which were surrounded by the extracellular matrix. Treatment with nalidixic acid, streptomycin, tetracyclin, ethylenediaminetetraacetic acid (EDTA) and dimethyl sulfoxide (DMSO) significantly (p < 0.05) inhibited the viability of C. pseudotuberculosis biofilm. The present study suggests that the biochemical composition of C. pseudotuberculosis biofilm may vary across different developmental stages. Meanwhile, nalidixic acid, streptomycin, tetracyclin, EDTA and DMSO may be useful in the treatment of CLA.